PENGARUH KETERLIBATAN KELUARGA DALAM BISNIS TERHADAP STRATEGI DAN KOMPENSASI CEO (Studi Empiris pada Perusahaan Non-Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2020) - Lia Magfiroh; Agung Juliarto (Diponegoro Journal of Accounting, 2022)
Family companies still dominate business in almost all countries around the world, including Indonesia. In various literatures it is explained that families have the power to influence and make important decisions for business. This study aims to examine the effect of family involvement in business on strategy and CEO compensation. In this research, family involvement was measured by using family ownership and family management. While, the dependent variables used were strategy and CEO compensation. In the addition, company size and company age were added as control variables. The sample in this study is non-financial companies listed on the Indonesia Stock Exchange from 2017-2020 with total samples are 196 obsevations. The sample selection based on the purposive sampling method and multiple linear regression analysis is used as the method of analysis in this study. The results of this study show that family ownership and family management have a negative effect on strategy. Moreover, family ownership and family management have a positive effect on CEO compensation. The priority of the family to prosper and protect the interests of the family makes the company adopt a conservative strategy and pay high CEO compensation, thereby showcasing the application of behavioral agency theory.